An Empirical Study of Ethical Fund Performance and Its Relation with Fund Characteristics - Chen, Jiaqi (2013)
The increasingly popularity of social responsible investing is a remarkable phenomenon of recent decades. And ethical funds have experienced rapid growth around the world. The evaluation of ethical fund performance has been achieving a lot of academic interests. This study employed a time series data to examine the influence of market status and fund characteristics on the performance of ethical funds. Three mutual fund performance measurements are utilized in this study, which are 1-factor model from Sharp (1964) and Lintner (1965), 3-factor model from Fama and French's (1993), and 4-factor model from Carhart (1997). Mature, growing, and initial market statuses and fund characteristics which are fund size, age, expense ratio and social performance, are analysed and testes whether they have influences on the performance of ethical funds. This study obtains some findings. Market status has a significant influence on ethical fund performance. And fund characteristics have different effects on performance in different markets. There are two more interesting findings: a critical value exists in both fund size and fund social performance. Keywords: SRI, ethical funds, financial performance, fund characteristics, social performance